In Vitro Photodynamic Studies of a BODIPY‐Based Photosensitizer. Issue 1 (15th December 2016) - Kim, Bosung; Sui, Binglin; Yue, Xiling; Tang, Simon; Tichy, Michael G.; Belfield, Kevin D.
Abstract : A new halogenated 4, 4‐difluoro‐4‐bora‐3a, 4a‐diaza‐ s ‐indacene (BODIPY) derivative was designed as a singlet‐oxygen photosensitizer (PS) for use as a photodynamic therapy (PDT) agent, and its photophysical properties were characterized. The PS, having two iodine atom substituents, exhibited a low fluorescence quantum yield ( Φ FL ) of 0.02 and high singlet‐oxygen‐generation quantum yield ( Φ Δ ) of 0.93. Furthermore, in vitro photodynamic activities were evaluated to assess the potential of using the PS for PDT. A propidium iodide (PI) fluorescence assay and live‐cell imaging of Lewis lung carcinoma (LLC) cells demonstrated that the cellular damage is induced by the photosensitization of the BODIPY dye, which subsequently leads to cell death by necrosis.q Abstract : Facile synthesis of an iodinated 4, 4‐difluoro‐4‐bora‐3a, 4a‐diaza‐ s ‐indacene (BODIPY) derivative exhibited highly efficient singlet‐oxygen sensitization. Photodynamic‐therapy activity experiments showed photo‐induced necrotic cell death in Lewis lung carcinoma cells.